2019
DOI: 10.3390/ijerph17010172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality Traits and Its Interaction with the Phenomenon of Bullying: Multi-Centre Descriptive Study

Abstract: Bullying affects thousands of teenagers worldwide and has devastating consequences. Various studies suggest that the personality of teenagers is a risk profile for bullying. The aim of this study was to analyse the relationship between the personality of teenagers aged 14 to 16 years from three education centres located in the province of Seville (Spain) and bullying in any of its victim or aggressor roles. A multi-centre cross-sectional observational descriptive study was conducted in three education centres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Neuroticism is a personality trait component that shows a statistically significant relationship with moral disengagement among adolescents. In line with a recent study conducted by Pabón-Carrasco et al (2020), which found that high neuroticism is associated with moral disengagement among adolescents, the present study confirms this association. Furthermore, the findings corroborate previous research conducted by Sattler and Schunck (2016), which found that respondents who scored low on conscientiousness but high on neuroticism are more likely to have used drugs in the past and are more likely to use drugs in the future than the general population.…”
Section: Figure 1 Mediation Model Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Neuroticism is a personality trait component that shows a statistically significant relationship with moral disengagement among adolescents. In line with a recent study conducted by Pabón-Carrasco et al (2020), which found that high neuroticism is associated with moral disengagement among adolescents, the present study confirms this association. Furthermore, the findings corroborate previous research conducted by Sattler and Schunck (2016), which found that respondents who scored low on conscientiousness but high on neuroticism are more likely to have used drugs in the past and are more likely to use drugs in the future than the general population.…”
Section: Figure 1 Mediation Model Discussionsupporting
confidence: 93%
“…A recent study conducted by Pabón-Carrasco et al (2020) analysed the relationship between personality and bullying among ninety-three 14-to-16-year-old students. This study found both anti-social behaviour and neuroticism to be significantly greater among bullies as compared to victims.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, findings from the ALSPAC cohort in over 5000 participants showed no association between the risk of exposure to bullying and PRS N (Schoeler et al, 2019). Previous reports showed an association between bullying and neuroticism (Rosta & Aasland, 2018), as well as an association between neuroticism and being an aggressor (Pabon-Carrasco et al, 2019). Furthermore, there has been plenty of research on the link between neuroticism and depression (Christensen & Kessing, 2006), but research on the interaction between neuroticism and exposure to bullying yields some contradictory results.…”
Section: Discussionmentioning
confidence: 94%
“…In them, bullying situations derived from the pressure to demonstrate more power among peers are observed [ 19 , 20 ]. In this sense, it is necessary to describe the personality of the aggressors, who may present diverse characteristics that may include aggressiveness towards the rest of the students and even adults, leadership charisma and strong temperament, observing in most cases an absence of empathy towards the victim [ 21 , 22 ]. The literature also identifies bullying scenarios far from the educational center, reporting bullying behaviors experienced by minors in their homes or social and cultural environments [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%